Blockchain governance - De Filippi, Primavera; Mannan, Morshed 1990-; Reijers, Wessel 1989- (Cambridge, Massachusetts The MIT Press, 2024)
"Blockchain Governance offers an accessible, critical overview of legal and political issues related to blockchain technology. It moves beyond the hype, showing how blockchain offers a fertile ground for experimentation with radically new ways to govern people and institutions"--
New Cambrian explosion -- Blockchain -- Rule of code -- Problem of trust -- States of exception -- Alegality -- Legitimacy -- Cryptopia.
Includes bibliographical references and index.
Keywords: Internet governance; Technology and law; Blockchains (Databases) -- Government policy